Coil embolization of asymptomatic left gastric artery aneurysm: Case report and literature review. Issue 5 (11th March 2023) - Jia, Heyue; Xi, Yifu; Yuan, Pengfei; Guo, Wei; Xiong, Jiang
Abstract: Patients with visceral artery aneurysms are rare, and the reported incidence of left gastric aneurysm (LGA) is only 4%. At present, although there is little knowledge about such disease, it is generally believed that appropriate treatment should be planned to prevent some dangerous aneurysms from rupturing. We introduced a case of 83‐year‐old patient with LGA who underwent endovascular aneurysm repair. The 6‐month follow‐up computed tomography angiography showed complete thrombosis in the aneurysm lumen. In addition, to insight the management strategy on LGAs deeply, a literature review concerning this entity published in recent 35 years was performed.